Numerical simulation of cement-treated soil reinforced with coir fiber subjected to flexural loading - Anggraini V.; Asadi A.; Huat B.B.K.; Syamsir A. (American Society of Civil Engineers (ASCE), 2023)
ABAQUS; Bending strength; Cements; Clay deposits; Elastic moduli; Fibers; Numerical analysis; Reinforcement; Safety engineering; Software testing; Soil cement; Soils; Steam turbines; Strength of materials; Cement treated soils; Coir fibers; Failure patterns; Flexural behavior; Marine clays; Plasticity indices; Potential failures; Three-point bending test; Forensic engineering